Epidural analgesia combined with a comprehensive physiotherapy program after Cytoreductive Surgery and HIPEC is associated with enhanced post-operative recovery and reduces intensive care unit stay: A retrospective study of 124 patients. Issue 12 (December 2016) - Osseis, M.; Weyrech, J.; Gayat, E.; Dagois, S.; Lo Dico, R.; Pocard, M.; Eveno, C.
Abstract: Background: Although Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) confers health benefits in peritoneal carcinomatosis (PC) treatment, it is associated with significant postoperative morbidity and mortality rate with increased length of hospital stay. The goal of this study is to determine whether a new comprehensive physiotherapy program including epidural loco-regional analgesia can improve the quality of care and patients recovery. Methods: Between 2009 and 2013, 124 patients with PC were operated for CRS and HIPEC procedures. These patients were analyzed and divided in 2 groups by means of time. No Physio group included patients operated from 2009 to 2011 (n = 57) having a thoracic patient controlled epidural analgesia (PCEA) but no preoperative physiotherapy program. The Physio group included patients operated from 2012 to 2013 (n = 67) having both a PCEA with a preoperative physiotherapy program. Results: The mortality rate was 1.6% (n = 2). The median length of stay in the intensive care unit (ICU) was lower in the Physio group, 2 days vs. 0 for No Physio group (p < 0.0001). The first time of mobilization after surgery was shorter in the Physio group (day 3 vs. 2, p = 0.0043). The overall satisfaction in the Physio group was achieved in 93% of patients, helping in decreasing fear of surgery and mobilization in 70% and 84% of cases respectively. Conclusion: Our study demonstrates that a clear pre-operative information and education by a physiotherapist, associated with a PCEA-pain management significantly benefits the patient's post-operative recovery and reduces the length of stay in the ICU.